Analisis Unsur Fisik dan Batin pada Puisi “Dalam Kenangan 1”, “Dalam Kenangan 2”, “Bersamamu Ketika Senja”, dan “Aku Menemuimu di Ujung Malam” Karya Heri Isnaini - Maria Yuniatun L. A; Hilmi Hikmatul A.; Nisa Ramadani (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This research aims to examine how the physical and mental elements in Heri Isnaini's poems entitled "Memories 1", "In Memories 2", "With You When Dusk", and "I Met You at the End of the Night". By focusing on the intrinsic analysis of the elements of poetry. The physical elements studied were diction, rhyme, majas, and typography. As for the inner element, it includes the theme, tone, atmosphere, and mandate implied in each work. The results of the analysis show that Heri Isnaini uses simple poetic language with a predominance of melancholy and contemplative atmospheres. The themes of love, silence, and memories become the common thread that connects the four poems. With the power of expression and subtle choice of diction, these poems reflect the poet's emotional depth towards both universal and personal experiences.